Implementasi Empat Pilar Program Corporate Social Responsibility (CSR) Pt Pasangkayu Dalam Peningkatan Ekonomi Masyarakat Pasangkayu - Siti Nurfadila; Lidya Olivia balanda; Fani Saudo; Zulvina Zulvina; Riskiyani Riskiyani; Almunawwara Almunawwara; Nanda Aprilia Royna; Rahmawati Halim; Syarif salingkat permana; Richard F. Labiro (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Corporate Social Responsibility (CSR) has become an important strategy for companies in supporting sustainable development and improving community welfare. This study aims to analyze the implementation of the four pillars of Corporate Social Responsibility programs carried out by PT Pasangkayu in improving the economic conditions of communities in Pasangkayu Regency. The four CSR pillars consist of education, health, environment, and economic empowerment. This research employed a qualitative descriptive approach with data collected through observation, interviews, and documentation. The findings indicate that PT Pasangkayu has implemented the four CSR pillars through various community-based programs. In the education sector, the company provides educational assistance and capacity-building activities. In the health sector, it supports public health services and preventive health programs. Environmental programs focus on environmental conservation and community awareness. Meanwhile, economic empowerment programs include entrepreneurship training, support for micro and small enterprises, and community-based economic development initiatives. The implementation of these programs has contributed to increasing community income, strengthening local economic activities, and improving community self-reliance. The study concludes that the successful implementation of CSR programs depends on collaboration among companies, local governments, and communities to achieve sustainable development goals.